y-3=2(x-9)

Rewrite the equation as 2(x-9)=y-3.

2(x-9)=y-3

Divide each term in 2(x-9)=y-3 by 2.

2(x-9)2=y2+-32

Cancel the common factor of 2.

Cancel the common factor.

2(x-9)2=y2+-32

Divide x-9 by 1.

x-9=y2+-32

x-9=y2+-32

Move the negative in front of the fraction.

x-9=y2-32

x-9=y2-32

Add 9 to both sides of the equation.

x=y2-32+9

To write 9 as a fraction with a common denominator, multiply by 22.

x=y2-32+9⋅22

Combine 9 and 22.

x=y2-32+9⋅22

Combine the numerators over the common denominator.

x=y2+-3+9⋅22

Simplify the numerator.

Multiply 9 by 2.

x=y2+-3+182

Add -3 and 18.

x=y2+152

x=y2+152

x=y2+152

Solve for x y-3=2(x-9)